"Truth, No Matter What": Why Watering Down Palestinian Reality Is a Crime - Baroud, Ramzy (The Washington report on Middle East affairs, 2023)
On Feb 20, 2023, the United Nations Security Council approved a statement, described in the media as a "watered-down" version of an earlier draft resolution, which would have demanded that Israel "immediately and completely cease all settlement activities in the occupied Palestinian territory." The intrigues that led to the scrapping of what was meant to be a binding resolution will be the subject of a future article. For now, however, Baroud would like to reflect on the tendency of the so-called international community to "water down" the horrific reality in which Palestinians live. While they often rage against statements made by US politicians who, like former Secretary of State Mike Pompeo, refuse to even acknowledge that Israel is occupying Palestine in the first place, they tend to forget that many of them are, somehow, involved in the watering down of the Palestinian reality, as well.